Home in the Poetry of Saudi Arabia Poets: Abdus-Salam Hafeth an Example of a Distinguished Arab (3) - Yahya Saleh Hasan Dahami (Universitas Islam Negeri Sumatera Utara Medan, 2022)
With particular reference to the Saudi poet Abdus-Salam Hashem Hafeth, this study tries to shed light on some literary characteristics of modern Saudi Arabic poetry. It specifically focuses on the concept of homeland as an illustration of the status of modern Saudi Arabic poetry. One may argue that Arabic poetry is in a good place right now among Arab authors, critics, and poets. By using the poet's magnificent city as a representation of his affection for his big country, the Kingdom of Saudi Arabia, the researcher attempts to demonstrate the poet's intelligence by showing his gorgeous city as a symbol of his love.An introduction starts the study, then, it analyzes the subtitle Arabic Poetry: The Tongue of the Arabs. Afterward, a brief analysis of Glimpse at Eternal Saudi Poetry and the Conception of Home in Saudi Poetry. The study's primary section employs a critical-analytical method to evaluate Abdus-Salam Hafeth's poem Nostalgia, Oh My Home. The examination of the poem concentrates on the idea of home as its central theme and covers verse lines nine through eleven. Finally, the research comes to a brief conclusion with some remarks.